Hatter M . [Volume one], The looking-glass wars - Beddor, Frank; Cavalier, Liz.; Templesmith, Ben, 1978- (Los Angeles : Automatic Pictures Pub., 2008)
By order of Queen Genevieve, Hatter Madigan, the Royal bodyguard, flees Wonderland with the princess, Alyss Heart, but when he loses Alyss in an alternate reality he embarks on a thirteen year quest to rescue her, and bring her back to the Wonderland realm.
"Volume 1: issues 1-4"--T.p. verso.
Booklist
Journal of Adolescent & Adult Literacy
Booklist, January 2009
Journal of Adolescent & Adult Literacy, April 2010
Young Adult.
Keywords: Hargreaves, Alice Pleasance Liddell, -- 1852-1934 -- Comic books, strips, etc. -- Juvenile fiction; Hargreaves, Alice Pleasance Liddell, -- 1852-1934 -- Fiction; Hargreaves, Alice Pleasance Liddell, -- 1852-1934 -- Comic books, strips, etc. -- Fiction; Bodyguards -- Comic books, strips, etc -- Juvenile fiction; Characters and characteristics in literature -- Comic books, strips, etc -- Juvenile fiction; Imagination -- Comic books, strips, etc -- Juvenile fiction; Princesses -- Comic books, strips, etc -- Juvenile fiction; Bodyguards -- Fiction; Cartoons and comics; Characters in literature -- Fiction; Fantasy; Imagination -- Fiction; Princesses -- Fiction; Bodyguards -- Comic books, strips, etc -- Fiction; Characters and characteristics in literature -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Graphic novels; Imagination -- Comic books, strips, etc -- Fiction; Princesses -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels